Communication skills intervention: promoting effective communication between nurses and mechanically ventilated patients - K. S. Dithole; Gloria Thupayagale-Tshweneagae; Oluwaseyi A. Akpor; Mary M. Moleki (BMC, 2017)
Abstract Background Patients in the Intensive Care Unit (ICU) often experience communication difficulties - usually associated with mechanical ventilation - resulting in psychological problems such as anxiety, fear, and depression. Good communication between nurses and patients is critical for success from personalised nursing care of each patient. The purpose of this study is to describe nurses' experience of a communication skills training intervention. Methods A convenience sample of twenty intensive care nurses participated in the study. Data was collected by means of interviews with nurses. Data from the interviews were analysed using qualitative thematic content analysis. Results Six themes emerged: (1) acceptance of knowledge and skills developed during workshops; (2) management support; (3) appreciation of augmentative and alternative communication (AAC) devices; (4) change in attitudes; and (5) the need to share knowledge with others and (6) inclusion of communication skills workshop training as an integral part of an orientation programme for all nurses. Conclusion The findings of this study indicated that the application of augmentative and alternative communication devices and strategies can improve nurse-patient communication in intensive care units. Therefore, the implementation of communication skills training for intensive care nurses should constantly be encouraged and, indeed, introduced as a key element of ICU care training.